Evaluation of vacuum washing in the removal of SDS from decellularized bovine pericardium: method and device description - Alizadeh, Morteza; Rezakhani, Leila; Soleimannejad, Mostafa; Sharifi, Esmaeel; Anjomshoa, Maryam; Alizadeh, Akram (Heliyon, 2019)
The aim of this study was to present a new method for removing Sodium dodecyl sulfate (SDS) detergent from decellularized bovine pericardium using vacuum. The cows’ pericardia were collected and decellularized. The samples were incubated with SDS1% for 48 h at 40 °C. To perform vacuum washing (VW: negative pressure was used to wash and remove detergents), every decellularized tissue was cut in 75mm diameter and fixed via a stainless-steel ring with 60mm diameter in the center of filtration Buchner Funnel which was connected to glass filtration flask The system was connected to a vacuum pump by a hose, and a negative pressure of -100 mmHg was applied for 15 min. Then, the samples were shaken and washed at 40-rpm in 100 ml of distilled water for 45 min. This process was repeated for samples of each group (6 times for sample VW6h, 12 times for sample VW12h, and 24 times for sample VW24h). At the end of every cycle, the effluent was collected to take a sample for SDS measurement. The normal washing (NW) group containing distilled water (NWd) and PBS (Phosphate buffered saline) (NWp) were used to wash and remove detergents. SDS measurements, MTT Assay, histological and tensile test, to compare two methods were used. The highest SDS in the effluent was in groups VW12h and VW24h (P ≤ 0.001) and the lowest residual SDS in scaffold was in two groups of VW12h and VW24h (P ≤ 0.001). MTT assay showed that cell survival in the VW12h and VW24h groups was higher than other groups and there' was no significant difference between cell survival in the VW12h and VW24h groups. Histological study showed destruction of tissue in the VW24h group. The results of the tensile test were shown that the native group had the highest module and the lowest amount was the VW24h sample which was reported with P ≤ 0.001 significance for all groups. VW12h can be used as an effective method for SDS removal from decellularized pericardium which morphologically demonstrated a good structure in ECM.